Theoretical perspectives on the international transfer and diffusion of climate technologies - Carsten Gandenberger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
Enhancing developing countries' access to climate technologies can provide a significant contribution to addressing climate change on a global scale. However, the issue of international technology transfer has remained underexplored in the climate policy literature and more research on the role of climate technology firms is needed. However, simply revisiting existing firm-level theories about the firm's internationalization behavior and technology transfer strategy with a view on climate technology would not be sufficient given that the objective is a widespread technology diffusion. In addition, these theories need to be closer aligned with the extant literature on knowledge spillover and technology diffusion which provides answers to the question why some developing countries are able to absorb foreign technology successfully, whereas others are not. Taking this as a starting point, the paper relates firm-level theories on internationalization and transfer channel choice to the literature on knowledge spillover and technology diffusion with the help of a simple framework. This framework is then applied to the issue at hand: the international transfer and diffusion of climate technologies. Implications are derived for climate technology firms as well as for the countries involved in the transfer process.
urn:nbn:de:0011-n-3546205
Keywords: 330; International Technology Transfer; Climate Technology; Transfer Channel; Knowledge Spillover; Technology Diffusion